2015
DOI: 10.1016/j.ijchp.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of an instrument to measure family disease management

Abstract: An instrumental study of 392 households with sick or disabled members was conducted to analyze the psychometric properties of the Family Disease Management Scale. Three different models were analyzed using the Confirmatory Factor Analysis (CFA). One was a single-dimensional factor (family disease management) with 30 items; and two hierarchical models with three factors, which represent the dimensions, family support, family normalization and family participation, that placed the workload into another of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Furthermore, with the inclusion of two symptomatology factors (psychological in the caregiver and behavioral in the patient), the IPSO-CA24 can subjectively evaluate the caregiver in other more objective facets of burden ( Pearlin et al, 1990 ). Apart from this, the knowledge caregivers have about the disease is related to their expectations ( Feldberg et al, 2011 ), the attitude with which they cope with situations derived from caregiving ( Saavedra et al, 2013 ), and therefore, how they manage the disease ( Lima-Rodríguez et al, 2015 ). Another of the components that directly influences the quality of caregiving is their reaction to the diagnosis ( Caron & Caron, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the inclusion of two symptomatology factors (psychological in the caregiver and behavioral in the patient), the IPSO-CA24 can subjectively evaluate the caregiver in other more objective facets of burden ( Pearlin et al, 1990 ). Apart from this, the knowledge caregivers have about the disease is related to their expectations ( Feldberg et al, 2011 ), the attitude with which they cope with situations derived from caregiving ( Saavedra et al, 2013 ), and therefore, how they manage the disease ( Lima-Rodríguez et al, 2015 ). Another of the components that directly influences the quality of caregiving is their reaction to the diagnosis ( Caron & Caron, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“… Feldberg et al (2011) suggested that the more negative the caregiver's beliefs are, the higher the probability of their experiencing overburdening and therefore, becoming more vulnerable to stress and anxiety. Training caretakers in symptomatology and the evolution of the disease, or in handling daily situations, could reduce overburden and even avoid its appearance ( Lima-Rodríguez et al, 2015 , Saavedra et al, 2013 ). Molinuevo and Hernández (2011) thought evolution of the patient's behavioral symptomatology is another of the factors determining how the caregiver copes with caregiving and the burden generated by it.…”
mentioning
confidence: 99%
“…In line with these results, Cronbach's Alpha Aan Yuliyanto 1) , Turmudi 2) , Ernawulan Syaodih 3) , Arie Dharmawan 4) , Cahya Karisma Pertiwi 5) , Idat Muqodas 6) , Dadan Rusdiana Saputra 7) 74| Volume 9, No 1, June 2021 ≥ 0.7 is considered acceptable (Xie, Li, Roos, Fong, Lo, Yeo, Yang, Chong, & Thumboo, 2006). Instrument with a Cronbach's Alpha value> 0.7 is considered reliable and can be used for further research (Astutik & Priantono, 2020;Bolarinwa, 2015;Lima-Rodriguez, Lima-Serrano, & Dominguez-Sanchez, 2015;Tsang, Royse, & Terkawi, 2017;Wells, Russell, Haraoi, Bissonnette, & Ware, 2011). Thus, the mathematical creative thinking skills instrument can reveal student responses that are not much different when applied to similar students even though it is implemented at different times and places.…”
Section: B Test the Reliability Of The Mathematical Creative Thinking Skills Instrumentmentioning
confidence: 59%
“…Sample sizes higher than 30 and smaller than 500 were considered suitable for most studies (Agung, 2006). A large representation of the sample would present more ◼ 5 intensity to the validation rule (Lima-Rodríguez, Lima-Serrano, & Domínguez-Sánchez, 2015).…”
Section: Methodsmentioning
confidence: 99%